D-Aspartic acid ameliorates painful and neuropsychiatric changes and reduces β-amyloid Aβ1-42 peptide in a long lasting model of neuropathic pain. (9th June 2017) - D'Aniello, Antimo; Luongo, Livio; Romano, Rosaria; Iannotta, Monica; Marabese, Ida; Boccella, Serena; Belardo, Carmela; de Novellis, Vito; Arra, Claudio; Barbieri, Antonio; D'Aniello, Biagio; Scandurra, Anna; et al.
Highlights: Increased levels of β-amyloid protein are shown in a long lasting model of neuropathic pain. Changed β-amyloid protein expression is associated with the appearance of behavioural dysfunctions. Thed -Aspartic acid treatment reduces pain and pain-associated neurological dysfunctions together with a normalization of the β-amyloid levels. Abstract: Depressive symptoms and other neuropsychiatric dysfunctions are common in neurodegenerative disorders, including chronic pain and dementia. A correlation between the β-amyloid protein accumulation and the development of depression has been suggested, however the underlying mechanisms are unknown.d -Aspartate (d -Asp) is a freed -amino acid found in the mammalian brain and involved in neurological and psychiatric processes, such as cognition and affective disorders. In this study we have investigated the effects of a repeated treatment withd -Asp in a long-lasting (12 months) model of neuropathic pain, the spared nerve injury (SNI), in mice. Specifically, we evaluated i) the pain sensitivity and related emotional/cognitive dysfunctions induced by SNI, ii) possible changes in the β-amyloid protein accumulation in specific brain regions involved in pain mechanisms ii) possible changes in steroids level in neuropathic animals with or withoutd -Asp in the same brain areas. SNI mice showed an increase of the insoluble form of Aβ1-42 at hippocampal level and displayed cognitive impairments, stereotypical and depressive-like behaviours.d -Asp treatment reduced abnormal behaviours and normalized the β-amyloid protein expression. Moreover, d -Asp dramatically increased steroids level measured in the prefrontal cortex and in the hippocampus. Our findings provide new insights into pain mechanisms and suggest a possible role of β-amyloid protein in neuropsychiatric dysfunctions associated with chronic pain.